Моделирование поражения стержня разрядом длинной искры с использованием многошаговой модели - Петков, Александр Александрович (НТУ "ХПИ", 2016)
Разработана многошаговая модель для определения вероятности поражения стержневого электрода, расположенного на плоскости, в полеобразующей системе электродов "стержень − плоскость". Показано, что предложенная модель позволяет адекватно описывать вероятность поражения стержневого объекта в разрядном промежутке длиной Н= 3 −15 м при соосном расположении электродов-стержней в полеобразующей системе. Близкие значения вариативного параметра Kst при моделировании наблюдаемых в экспериментах значениях вероятности поражения р* = 1 позволяют считать одинаковыми процессы, приводящие к поражению стержня вне зависимости от размеров электродной системы и параметров импульсов напряжения, применяемых при испытаниях. Материалы работы могут быть использованы для дальнейших исследований поражения длинной искрой объектов, расположенных на плоской поверхности.

Building a multi-step model, which allows to calculate the probability of hitting the rod object of a long spark. The object is located in an electric field, which is formed in the electrode system "rod-plane". Confirmation of adequacy of the model to experimental data, which describe the probability of hitting in the rod objects. Methodology. Numerical simulation of movement long sparks from a point in space in the direction of the plane. Comparison of the results of modeling of the probability of defeat of a rod with a confidence interval, which is determined on the basis of experimental data. Results. Developed multistage model adequately describes the probability of defeat the rods objects. In the simulation, the discharge gap has a length of Н = 3 − 15 m. The adequacy confirmed by the case where the long spark begins to develop from a point on the axis of the rod object. Originality. For the first time propositioned a mathematical model to determine the probability of defeat the rod object, which is based on multi-step procedure traffic long spark. Practical value. The developed model allows to predict the probability of defeat the rod of objects a length to 6 m.
Modeling defeat rod long spark discharge using a multi-step model
Keywords: математическая модель; вероятность поражения; доверительный интервал; mathematical model; probability of defeat; confidence interval